THE EFFECT OF UREA FERTILIZER DOSAGE ON THE GROWTH AND YIELD OF SOME VARIETIES OF SWEET SORGHUM (SORGHUM BICOLOR L.) - Ekowahyuni, Luluk Prihastuti; Gulo, Netral Eli (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to explore the potential of sorghum development in Indonesia by evaluating the interaction between different sorghum varieties and urea fertilizer dosages. The research employed a Randomized Complete Block Design (RCBD) with two treatment factors: three sorghum varieties (Bioguma 1, Bioguma 2, Bioguma 3) and four urea dosages (0, 50, 100, 150 kg/ha), resulting in 12 treatment combinations replicated three times. Conducted over four months in a sub-urban area of Jakarta, the site was characterized by warm temperatures, high humidity, and unstable weather conditions including rain and strong winds. Despite these challenges, sorghum plants showed consistent growth. The results revealed that the interaction between sorghum varieties and fertilizer dosages significantly influenced plant development. Among all combinations, Bioguma 3 treated with 150 kg/ha urea demonstrated the best performance. These findings emphasize the importance of selecting optimal variety and fertilizer combinations to enhance sorghum cultivation in similar agro-climatic regions.